Differential responses to the combination of navitoclax and venetoclax with doxorubicin in murine models of triple negative breast cancer - As Sobeai, Homood M.; Alanazi, Abdulrahman M.; Alotaibi, Faisal; Alhoshani, Ali; Alhazzani, Khalid; Almutairi, Mashal M.; Almudimeegh, Sultan; Al-Ramadi, Basel K.; Chakraborty, Eesha; Saleh, Tareq; Gewirtz, David A.; Harada, Hisashi; et al. (Frontiers in Cell and Developmental Biology, 2026)
IntroductionTherapy-induced Senescence (TIS) can potentially influence breast cancer treatment outcomes, in part by contributing to disease recurrence; hence, the utilization of senescence-eliminating agents (i.e., senolytics) is considered as a possible adjuvant to chemoradiation. However, one of the most effective senolytic agents, navitoclax (ABT-263), is limited by its associated toxicities of thrombocytopenia and neutropenia. In contrast, venetoclax (ABT-199), which is currently standard of care in CLL and AML, is of less senolytic potential. Moreover, a comparison between their combinational effect with standard chemotherapy in animal models of breast cancer is not widely explored. This study compared the senolytic potential of the two BH3 mimetics in combination with doxorubicin in two models of triple-negative breast cancer (4T1 and E0771 cells).MethodsSenescence was cytochemically confirmed via Senescence-associated β-galactosidase upregulation (and quantified by flow cytometry), CDKN1A induction, and the senescence-associated secretory phenotype (SASP) expression (using qRT-PCR). Cell viability and the percentage of apoptotic cells were determined using MTT and Annexin V/7AAD assays, respectively.ResultsBoth navitoclax and venetoclax were effective as apparent senolytics in the E0771 cells. In contrast, only navitoclax was effective against the 4T1 cells. The in vitro findings in E0771 cells were validated through studies conducted in vivo in immunocompetent mice implanted with E0771-derived tumors where both drugs reduced tumor progression and shifted cells to apoptosis in sequential combination with doxorubicin.ConclusionsThese findings suggest that administration of venetoclax has the potential to enhance suppression of doxorubicin-exposed cancer cells, and that it may have potential as that of Bcl-xL-targeting agents. However, given the variable outcomes in the two triple-negative breast tumor cell lines, it becomes incumbent to identify the factors that confer susceptibility to Bcl- 2 targeting agents in anticipation of their potential utilization in the clinic for combination therapy in solid tumors.